Afrocentrism effect on consumer perceptions - Case Study - Iwori Beauty - Ash, Tayla (The IIE, 2019)
This study explores whether Afrocentrism affects and influences consumers perceptions of brands and the products they use. This will be determined through analyzing African heritage-based brand – Iwori. Iwori expresses Afrocentrism throughout their brand and therefore, a conclusion will be based off whether Iwori has positive consumer perceptions in relation to their Afrocentric movements.This topic was approached through qualitative explanatory research because the findings are not factual but rather opinion and experienced based. The finds were enhanced through in-depth interviews with Iwori’s administration which provided insight into their marketing mix and how Afrocentrism is guided throughout their business and products produced. Questionnaires that were sent out to users of Iwori products gave insight about why consumers use the products, what attracted them to the product and their personal experiences with the brand.This study contributes to the research into whether expressing Afrocentrism throughout an individual’s business will positively influence a business’s customer base and the image that business creates.
Keywords: Brand; Brand image; Brand identity; Consumer behaviour